Rethinking Infrastructure Design for Multi-Use Water Services - Maksimović, Čedo (Springer, 2015)
As we approach a historic tipping point in the global trend toward urbanisation – within two decades urban dwellers will increase from 49% to 60% of the planet’s population – this book identifies and addresses a critical problem: water. The editors show how cities can shift from being water consumers to resource managers, applying urban water management principles to ensure access to water and sanitation infrastructure and services; manage rainwater, wastewater, storm water drainage, and runoff pollution; control waterborne diseases and epidemics; and reduce the risk of such water-related hazards as floods, droughts and landslides.